Electrical mapping in bipolar disorder patients during the oddball paradigm. (January 2016) - Di Giorgio Silva, Luiza Wanick; Cartier, Consuelo; Cheniaux, Elie; Novis, Fernanda; Silveira, Luciana Angélica; Cavaco, Paola Anaquim; de Assis da Silva, Rafael; Batista, Washington Adolfo; Tanaka, Guaraci Ken; Gongora, Mariana; Bittencourt, Juliana; Teixeira, Silmar; et al.
Abstract: Bipolar disorder (BD) is characterized by an alternated occurrence between acute mania episodes and depression or remission moments. The objective of this study is to analyze the information processing changes in BP (Bipolar Patients) (euthymia, depression and mania) during the oddball paradigm, focusing on the P300 component, an electric potential of the cerebral cortex generated in response to external sensorial stimuli, which involves more complex neurophysiological processes related to stimulus interpretation. Twenty-eight bipolar disorder patients (BP) (17 women and 11 men with average age of 32.5, SD: 9.5) and eleven healthy controls (HC) (7 women and 4 men with average age of 29.78, SD: 6.89) were enrolled in this study. The bipolar patients were divided into 3 major groups (i.e., euthymic, depressive and maniac) according to the score on the Clinical Global Impression – Bipolar Version (CGI-BP). The subjects performed the oddball paradigm simultaneously to the EEG record. EEG data were also recorded before and after the execution of the task. A one-way ANOVA was applied to compare the P300 component among the groups. After observing P300 and the subcomponents P3a and P3b, a similarity of amplitude and latency between euthymic and depressive patients was observed, as well as small amplitude in the pre-frontal cortex and reduced P3a response. This can be evidence of impaired information processing, cognitive flexibility, working memory, executive functions and ability to shift the attention and processing to the target and away from distracting stimuli in BD. Such neuropsychological impairments are related to different BD symptoms, which should be known and considered, in order to develop effective clinical treatment strategies. Highlights: Higher P300 amplitude in healthy controls, low P300 amplitude in manic patients. Similar P300 amplitude and latency in euthymic and depressive patients. Manic group showed the smallest P300 amplitude, mainly for the frontal electrodes. Small P300 amplitude for the pre-frontal area electrodes can be related to an impairment of cognitive flexibility. This study provided a evidence of a delay in the information processing and reduced attention allocation of bipolar patients.